2022
DOI: 10.47709/digitech.v2i2.1779
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kinerja Load Balancing Terhadap Jaringan Internet Menggunakan Metode Equal Cost Multi Path (ECMP)

Abstract: Load balancing on Mikrotik is a technique for distributing loads network traffic on two or more connection lines in a balanced way, so that network traffic can run optimally, maximize transfer speed, reduce response time and avoid excessive capacity usage on one connection line. There are various methods that can be used in load balancing, one of which is the ECMP method. ECMP is a load balancing method that is used to divide the traffic of two or more internet connections with the same load on each line. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…One proof of this development is the increasing number of users of Interconnected Networks (Internet), especially in Indonesia. The changes that people experience with the existence of the internet certainly have an impact on various lines of life, starting from individuals, agencies, companies, and private organizations the government also takes advantage of the sophistication of internet technology, because with the internet people are able to carry out interactions and transactions [1]. According to data released by the Asosiasi Penyelengara Jasa Internet Indonesia (APJII) in 2020, it was found that the number of Internet users in Indonesia reached 196.71 million [2].…”
Section: Introductionmentioning
confidence: 99%
“…One proof of this development is the increasing number of users of Interconnected Networks (Internet), especially in Indonesia. The changes that people experience with the existence of the internet certainly have an impact on various lines of life, starting from individuals, agencies, companies, and private organizations the government also takes advantage of the sophistication of internet technology, because with the internet people are able to carry out interactions and transactions [1]. According to data released by the Asosiasi Penyelengara Jasa Internet Indonesia (APJII) in 2020, it was found that the number of Internet users in Indonesia reached 196.71 million [2].…”
Section: Introductionmentioning
confidence: 99%